Toward a Better Understanding of the Atypical Features of Chronic Graft-Versus-Host Disease: A Report from the 2020 National Institutes of Health Consensus Project Task Force - Cuvelier, Geoffrey D.E.; Schoettler, Michelle; Buxbaum, Nataliya P.; Pinal-Fernandez, Iago; Schmalzing, Marc; Distler, Jörg; Penack, Olaf; Santomasso, Bianca D.; Zeiser, Robert; Angstwurm, Klemens; MacDonald, Kelli P.A.; Kimberly, W. Taylor; et al. (Transplantation and Cellular Therapy, 2022)
Alloreactive and autoimmune responses after allogeneic hematopoietic cell transplantation can occur in nonclassical chronic graft-versus-host disease (chronic GVHD) tissues and organ systems or manifest in atypical ways in classical organs commonly affected by chronic GVHD. The National Institutes of Health (NIH) consensus projects were developed to improve understanding and classification of the clinical features and diagnostic criteria for chronic GVHD. Although still speculative whether atypical manifestations are entirely due to chronic GVHD, these manifestations remain poorly captured by the current NIH consensus project criteria. Examples include chronic GVHD impacting the hematopoietic system as immune mediated cytopenias, endothelial dysfunction, or as atypical features in the musculoskeletal system, central and peripheral nervous system, kidneys, and serous membranes. These purported chronic GVHD features may contribute significantly to patient morbidity and mortality. Most of the atypical chronic GVHD features have received little study, particularly within multi-institutional and prospective studies, limiting our understanding of their frequency, pathogenesis, and relation to chronic GVHD. This NIH consensus project task force report provides an update on what is known and not known about the atypical manifestations of chronic GVHD while outlining a research framework for future studies to be undertaken within the next 3 to 7 years. We also provide provisional diagnostic criteria for each atypical manifestation, along with practical investigation strategies for clinicians managing patients with atypical chronic GVHD features.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Atypical; Chronic graft-versus-host disease; National Institutes of Health Consensus Project Task Force